Kelas Bilingual dan Reproduksi Identitas Kelas Menengah: Studi Pada SMP Berkurikulum Nasional - Naura Rifa Salsabila; Muh. Hanif (CV Edujavare Publishing, 2026)
This article examines the implementation of bilingual classes in junior high schools (SMP) adopting the national curriculum (Kurikulum Merdeka) as a strategy for reproducing middle-class identity within local communities. Using a qualitative approach with an interpretive case study design at SMP SAMBAS in the Purbalingga region, this study investigates how educational institutions convert economic capital into cultural capital through bilingual education. The findings reveal three main mechanisms of social reproduction. First, the bilingual program functions as a means of accumulating cultural capital through different levels of bilingual learning intensity among student groups. Second, English operates as a form of symbolic capital that contributes to the construction of social hierarchies within the classroom. Third, alumni networks and institutional support provide an infrastructure that reinforces the reproduction of middle-class identity. The study concludes that bilingual programs within the framework of the national curriculum can reproduce class advantages and strengthen middle-class aspirations while maintaining the relevance of national education in the context of globalization. These findings contribute to the sociology of education by demonstrating how schools reproduce social differentiation through language-based educational programs.